Risk factors associated with external apical root resorption of the maxillary incisors: a 15-year retrospective study - Rakhshan Vahid; Nateghian Nazanin; Ordoubazari Morteza (Sciendo, 2012)
Aim: To determine the possible risk factors for external apical resorption (EARR) of the maxillary incisors.